(untitled) - Skehan, Peter (Oxford, 1998)
This book addresses issues such as the relation of form to meaning, the relevance of SLA research, and the validity of task-based learning. It also contrasts universalist accounts of language learning and individual differences between learners
Keywords: Second language acquisition,Cognitive learning theory